Senior high school students’ understanding of Newton’s laws in outer space: Identification of misconceptions - Winarti, Winarti; Pardiyanto, Eko; Kurnianto, Fajar (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
One of the most frequently observed explanations in misconceptions is conceptual understanding. This research aimed to determine the senior high school students’ conceptual understanding of Newton’s laws in outer space. The researchers assumed that the research results would be rich in variation by elaborating the item questions based on the precise step of Digital Story Conceptual Change-Oriented as a learning medium. The researchers researched State Senior High School 5 Yogyakarta. The participants of this study consisted of 91 students. The applied instruments were fifteen two-tier multiple-choice items. The researchers also used a non-test instrument, namely an interview sheet. The researchers found related misconceptions in Newton’s law in outer space during the research. It was found that 30% of students experienced misconceptions. The results are important for the learning process that through identification, teachers could use strategy to explain the materials.